A justicialidade dos direitos fundamentais nos contratos privados de assistência à saúde - Lima, Leonardo Franco de (2016)
Many were the battles fought for all humanity throughout the ages for recognition of various human rights. The 1988 Federal Constitution, inspired by other European legal systems, especially the Portuguese, brought great progress in the recognition of numerous social rights, aside from concern to confer instruments so these rights could be implemented by the state and the whole society in order that the precepts planted in the constitution were not relegated to mere promises. The health rights is among those the constitutional legislator leaned more concern, not limited to grant it as a public subjective right, but also organized a unique system through regionalized and hierarchical network, involving all political federation entities and the society as responsible for its implementation. This paper assumes that health is a public subjective right, allowing this way its judicial protection. Inclusive, from this point of view, the pact's preamble that established the World Health Organization conceives health as a state of complete physical, mental and social well-being, obliging the Brazilian State to guarantee its citizens all means for health preservation or re-establishment. However, the 1988 Federal Constitution opened to private sector the pportunity to participate in the health system, both in its complementary form, working with the public health system through the execution of public contract or celebrating agreement with the administration, as in supplemental way through private services provided by contracting health insurance providers. This pact should be analyzed from the perspective of another fundamental right, as elected by the 1988 Letter, the consumer right. This way, it is essential to establish the distinction between public and private orms for health rights exercise, through harmonisation between the principles of human dignity and the right to health with other constitutional principles as those who consecrate the private autonomy, legal certainty, the property, free enterprise, the separation of powers, among others. This interpretative task with its various technical analysis allows you to extract from the current laws the conformation between the rules and principles that establish the limits of each legal relationship, private and public, demonstrating an improper intervention of judiciary in fields given for legislators